A Copper(II) Phenanthroline Metallopeptide That Targets and Disrupts Mitochondrial Function in Breast Cancer Stem Cells. (5th December 2017) - Laws, Kristine; Bineva‐Todd, Ganka; Eskandari, Arvin; Lu, Chunxin; O'Reilly, Nicola; Suntharalingam, Kogularamanan
Abstract: The breast cancer stem cell (CSC) and bulk breast cancer cell potency of a series of metallopeptides containing dichloro(1, 10‐phenanthroline)copper(II) and various organelle‐targeting peptide sequences is reported. The mitochondria‐targeting metallopeptide1 exploits the higher mitochondrial load in breast CSCs over the corresponding non‐CSCs and the vulnerability of breast CSCs to mitochondrial damage to potently and selectively kill breast CSCs. Strikingly, 1 reduces the formation and size of mammospheres to a greater extent than salinomycin, an established CSC‐potent agent. Mechanistic studies show that1 enters CSC mitochondria, induces mitochondrial dysfunction, generates reactive oxygen species (ROS), activates JNK and p38 pathways, and prompts apoptosis. To the best of our knowledge, 1 is the first metallopeptide to selectivity kill breast CSCs in vitro.